Everyone brave is forgiven [compact disc, unabridged] - Cleave, Chris (Simon & Schuster Audio, 2016)
London, 1939. The day war is declared, Mary North leaves finishing school unfinished, goes straight to the War Office, and signs up. Tom Shaw decides to ignore the war, until he learns his roommate Alistair Heath has unexpectedly enlisted. Then the conflict can no longer be avoided. Young, bright, and brave, Mary is certain she'd be a marvelous spy. When she is, bewilderingly, made a teacher, she finds herself defying prejudice to protect the children her country would rather forget. Tom, meanwhile, finds that he will do anything for Mary.